TERAPI AKTIVITAS KELOMPOK PADA LANSIA DENGAN MEDIA TEBAK GAMBAR UNTUK MENGATASI PENURUNAN FUNGSI KOGNITIF DI PANTI WREDHA KASIH AYAH BUNDA KOTA TANGERANG - Alfika Safitri; Anik Widiastuti; Afrina Kusuma Dewi; Imas Permasi; Dwi Setyawati; Ati Setiawati; Tsani Dermawan; Yeni Gumiati; Chaerunnisa Eka Sania (Nusantara Hasana Journal, 2024)
Group activity therapy is one of the therapeutic modalities carried out by nurses for groups of elderly people who have the same nursing problems. Group activities for elderly people who have the same nursing problems. Activities are used as therapy and groups as targets of care. Guess the picture is a light brain teaser game, tests imagination, logic and reasoning, guess the picture is a form of game where from the results of this game participants can enjoy the activities they do so that the game can reduce boredom and can assess gross motor skills, fine motor skills, language, cognitive and socialization according to age level. Activity Objective: It is hoped that elderly people can train their sensory, motor and cognitive abilities with cognitive therapy in the form of guessing pictures. Activity Method: Providing Group Activity Therapy by guessing pictures, TAK is carried out on clients with physical conditions that allow it (for example: being able to move body parts such as hands), clients who are managed by students of the Yatsi Madani University Nursing professional program and cooperative clients. Activity Results: Observation results showed that the elderly were cooperative and every question from the team was answered well by the elderly with the picture in question. The achievement of the target of the picture guessing group therapy activity was quite good, because the material was delivered in its entirety (100%).